2016
DOI: 10.2147/phmt.s119958
|View full text |Cite
|
Sign up to set email alerts
|

Adopted youth and sleep difficulties

Abstract: Sleep is a critical component of healthy development for youth, with cascading effects on youth’s biological growth, psychological well-being, and overall functioning. Increased sleep difficulties are one of many disruptions that adopted youth may face throughout the adoption process. Sleep difficulties have been frequently cited as a major concern by adoptive parents and hypothesized in the literature as a problem that may affect multiple areas of development and functioning in adopted youth. However, there i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 96 publications
0
3
0
Order By: Relevance
“…Internationally adopted children could therefore be at risk. Although many adoptive parents report a sleep problem in their children, 2 5 these studies have not focused on sleep specifically or used validated sleep questionnaires. To the best of our knowledge, two studies in adopted children used validated sleep questionnaires.…”
Section: Dear Editormentioning
confidence: 99%
“…Internationally adopted children could therefore be at risk. Although many adoptive parents report a sleep problem in their children, 2 5 these studies have not focused on sleep specifically or used validated sleep questionnaires. To the best of our knowledge, two studies in adopted children used validated sleep questionnaires.…”
Section: Dear Editormentioning
confidence: 99%
“…First, poverty in the family is an additional source of stress and is connected with limited access to sports in free time. Second, the authors of many studies have found that sharing a bed or bedroom with siblings or parents has a significant adverse effect on the duration and quality of sleep among young people [15]. On the other hand, a TV set, computer and audio-video equipment in a teenager’s room also constitutes a sleep disrupting factor [16].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent study, almost a third of adolescents adopted in childhood had insomnia and this proportion was significantly larger than in their non-adopted controls (14). Pre-adoptive stress, lack of parental care, deprived living conditions in institutions, and major changes during the adoption transition have been suggested as risk factors for sleep disturbances in adopted children (6,(15)(16)(17).…”
Section: Introductionmentioning
confidence: 99%